1976
DOI: 10.1095/biolreprod14.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Control of the LH Receptor by Prolactin and Prostaglandin F2α in Rat Corpora Lutea

Abstract: Functional corpora lutea were induced in 28 day old, female rats with 4 iu of pregnant mare's serum, followed 72 h later with cervical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(22 citation statements)
references
References 19 publications
5
17
0
Order By: Relevance
“…LH receptors in swine and bovine corpora lutea have been reported to decrease immediately after PGF 2α administration [35,36] and continue to decline during the following 24 h; a similar trend has been reported, at least in swine, for both luteal and serum progesterone concentrations, so that all these parameters present a similar profile. The results from this study, on the contrary, indicate that both plasma and luteal P4 concentrations diminish before the reduction of LHr mRNA (which seems to be more related to the reduction in CL weight); these data are in agreement with those by Grinwich et al [37], who observed that the drop in luteal LH receptors in PGF 2α -treated rats is less pronounced than that of progesterone concentrations. Also Spicer et al [38] in the cow, Diekman et al [39] in the sheep and Roser et al [40] in the mare reported that the drop in blood progesterone levels precedes by several hours the drop in LH receptors or hCG binding sites in CL from PGF 2α -injected animals.…”
Section: Parameterssupporting
confidence: 92%
See 1 more Smart Citation
“…LH receptors in swine and bovine corpora lutea have been reported to decrease immediately after PGF 2α administration [35,36] and continue to decline during the following 24 h; a similar trend has been reported, at least in swine, for both luteal and serum progesterone concentrations, so that all these parameters present a similar profile. The results from this study, on the contrary, indicate that both plasma and luteal P4 concentrations diminish before the reduction of LHr mRNA (which seems to be more related to the reduction in CL weight); these data are in agreement with those by Grinwich et al [37], who observed that the drop in luteal LH receptors in PGF 2α -treated rats is less pronounced than that of progesterone concentrations. Also Spicer et al [38] in the cow, Diekman et al [39] in the sheep and Roser et al [40] in the mare reported that the drop in blood progesterone levels precedes by several hours the drop in LH receptors or hCG binding sites in CL from PGF 2α -injected animals.…”
Section: Parameterssupporting
confidence: 92%
“…As suggested [38], the decrease in LH receptors does not seem to be the first step in corpora lutea regression which is likely associated to other events such as a direct antagonism of LH by PGF 2α [37]. These authors hypothesized that the very rapid effect of prostaglandins on progesterone secretion probably occurs through a reduction in the LH-induced hyperemic activity at the ovarian level; the loss of LH receptors possibly ensures the subsequent progression of the luteolytic process.…”
Section: Parametersmentioning
confidence: 92%
“…Thus, it can be argued that inhibition of hormone action may be the actual response to prostaglandins in luteal cells rather than the mediation of LH action in mouse ovarian tissue suggested by Kuehl et al (11). In vlvo, the ovary is constantly exposed to LH and, in the absence of this gonadotropin, luteal progesterone production rapidly wanes (16 (3) and in cultures of porcine, bovine, and human luteinized granulosa cells exposed to PGF2o, for several hours (18 (2,6). From the present data it is concluded that the rapid effect of PGF2 on progesterone secretion, which occurs in minutes, is due to inhibition of LH-dependent cAMP accumulation and not to inhibition of LH binding to its receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Hichens et al (5) demonstrated such an action of PGF2< but, in later studies, Grinwich et al (6) found that the loss of LH receptors occurred several hours after the decrease in circulating progesterone. Thus, the loss of LH receptors may explain the long-term antigonadotropic action of PGF2,r in vio, but the acute action of PGF2<, appears to be independent of the number of LH binding sites in luteal tissue.…”
mentioning
confidence: 97%
“…Some of the current studies which are germane to this area are: the effects of PGF2, upon LH receptor mechanisms (47), the role of estrogen in prostaglandin-induced luteolysis (48,49) as well as the direct effects of estradiol upon luteal cell progesterone secretion (50), and the role of lysosomes in luteal regression (51).…”
Section: Luteolytic Controlmentioning
confidence: 99%